Orientation of the emotional meanings of teachers during their work in the classroom - Poblete-Christie, Octavio (Revista de Sociología, 2021)
This article presents some of the results of research into various aspects of the emotional experience of classroom teachers. Specifically, the results were obtained through analysis of the meanings constructed in relation to their work. We used a qualitative approach and a design based on emotional episodes, that is, concrete classroom situations that provoked emotions in teachers. Four primary school mathematics and Spanish language teachers from two institutions participated. We used semi-structured interviews as data construction techniques. We studied twenty episodes, conducting twenty interviews, one for each episode. The content analysis yielded various meanings that explained the emergence of the emotions experienced, from which we were able to construct three categories: external, internal, and mixed. We discuss the implications based on psychological, educational, and epistemological criteria.